Monetary and financial integration: lesson from the European Union - Urrunaga, Roberto; Silva, Jessica (Universidad del Pacífico, 1998)
This article discusses the integration process of the European Union, stressing the financial aspects, and also discusses the need for a single currency as a further step in that process. The analysis of the financial integration evaluates the existence of interest rate parity and convergence. The main result is that both parity and convergence seem to have been achieved, but only for long run interest rates and just recently. The persistence of important differences between short run interest rates could cause some troubles and it would be showing the skepticism of the single currency successful. Also, the article carries out that the implementation of the single currency will reduce the autonomy of the fiscal policy, and mainly the tax policy, something that appears unwanted by the authorities of the country members of the European Union that have avoided to establish agreements about that.